The AaLplus near-peer teaching program in family medicine strengthens basic medical skills: a five-year retrospective study - Schwill, Simon; Hundertmark, Jan; Fahrbach-Veeser, Johanna; Eicher, Christiane; Tonchev, Pencho; Kurczyk, Sonia; Szecsenyi, Joachim; Loukanova, Svetla (PLOS ONE, 2020)
Background Basic medical skills such as history taking and physical examination are essential components of clinical work profiles, but nevertheless have been neglected by conventional pre clinical curricula. The near-peer-teaching program AaL(plus) [living anatomy plus] teaches basic medical skills, especially history taking, physical examination, and venepuncture, to preclinical students. It is a highly popular compulsory course in the first four semesters (320 students/year, 9h/semester) at Heidelberg University and ends with a formative Objective Structured Clinical Examination (OSCE) during which students receive structured in-depth feedback on their performance. AaL(plus) is part of the Department of General Practice's longitudinal curriculum for Family Medicine. Objectives This study aims to assess whether the AaL(plus) program has positive effects on students' clinical skill development and subjective confidence in history taking, physical examination and venepuncture. Methods From 2015 to 2019, we asked all AaL(plus) participants to rate the program and self-assess their medical skills on 5-point Likert scales (min 1, max 5). In 4-station OSCEs, trained tutors rated the students' performance in all taught skills using standardized checklists. Results From 2015 to 2019 n = 1534 questionnaires returned (response rate = 98.6%, 52.7% females). After course completion, students felt able to take a patient's history (mean 3.97, SD = 0.75) and perform physical examinations (means range 3.82-4.36, SDs range 0.74-.89) as well as venepuncture (mean 4.12, SD = 0.88). A large majority of students claimed they acquired these skills in the AaL(plus) program. During OSCE, 81.9% passed anamnesis, 93.1% passed physical examination, and 95.4% passed venepuncture (of n = 1556). Students mostly rated the feedback they received during the OSCE as "helpful" or "very helpful" (means for different stations 4.69-4.76, SDs 0.50-0.70). Conclusions AaL(plus) is a positive example of a peer teaching program in the preclinical stage of medical studies. It successfully trains junior students in essential medical abilities and increases their confidence in their skills. A high percentage of students pass the formative OSCE and evaluate it positively. Consistently high ratings indicate the program's routine viability. Further studies are needed to analyze if programs like AaL(plus) could have an impact on the number of graduates choosing career in Family Medicine.